Perioperative anaesthetic challenges in coronavirus disease associated mucormycosis: A retrospective study - Mamta Khandelwal; Sunita Meena; Sanjay Morwal; Priyanka Jain; Yogesh Modi (Creative Pharma Assent, 2022)
Background & Aim: Mucormycosis is a life-threatening fungal infection that occurs in immune-compromised patients. There were large number of mucormycosis cases reported during COVID pandemic (2019-21) mainly as post COVID sequelae. In the present retrospective study we aimed to evaluate the perioperative challenges faced in the anaesthetic management of Coronavirus disease associated Mucormycosis (CAM) patients who underwent surgery under general anesthesia. Methods: The perioperative records of CAM patients who underwent surgery from May 2021-July 2021 for mucormycosis were reviewed and evaluated in terms of difficult bag mask ventilation, difficult intubation and other intraoperative and post-operative complications. Observation and Results: The incidence of CAM and its associated surgery was significantly more in males than females and the mean age of the patients was 50 years. In 39.8% patients we encountered difficult bag mask ventilation. and in 17.5% patients more than two attempts for intubation were required. Conclusion: Mucormycosis patients posted for surgery may pose various anesthetic challenges especially in airway management and anesthesiologists must be well prepared for it